2020
DOI: 10.3389/fphar.2020.603104
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exosomal Non-Coding RNAs in Coronary Artery Disease

Abstract: Cardiovascular disease (CVD) remains the leading cause of morbidity and mortality worldwide. Atherosclerosis (AS) is a major cause of CVD. Oxidative stress, endothelial dysfunction, and inflammation are key factors involved in the development and progression of AS. Exosomes are nano-sized vesicles secreted into the extracellular space by most types of cells, and are ideal substances for the transmission and integration of signals between cells. Cells can selectively encapsulate biologically active substances, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 149 publications
0
18
0
Order By: Relevance
“…The communication between exosomal miRNAs and ECs plays a vital role in the pathogenesis of AS. 436 Exosomal miR-92a, upregulated by the combination of low shear stress and oxidized LDL in atherosclerotic mice model, promoted endothelial inflammation and atherosclerotic plaque formation. 437 Besides, Xing et al reported that exosomal miR-342-5p released by adipose-derived MSCs exerted an anti-atherosclerotic effect by promoting H 2 O 2 -induced ECs apoptosis and protecting against ECs injury.…”
Section: The Roles Of Exosomal Ncrnas In Human Diseasesmentioning
confidence: 99%
“…The communication between exosomal miRNAs and ECs plays a vital role in the pathogenesis of AS. 436 Exosomal miR-92a, upregulated by the combination of low shear stress and oxidized LDL in atherosclerotic mice model, promoted endothelial inflammation and atherosclerotic plaque formation. 437 Besides, Xing et al reported that exosomal miR-342-5p released by adipose-derived MSCs exerted an anti-atherosclerotic effect by promoting H 2 O 2 -induced ECs apoptosis and protecting against ECs injury.…”
Section: The Roles Of Exosomal Ncrnas In Human Diseasesmentioning
confidence: 99%
“…To analyze and quantify ncRNAs in exosomes and microvesicles, they must be isolated from platelet-depleted plasma (Liu et al, 2020). Isolation techniques differ between ncRNAs transported in EVs and those transported in ncRNAprotein complexes (Liu et al, 2020).…”
Section: The Non-coding Transcriptome As Biomarker: Challenges and Future Directionsmentioning
confidence: 99%
“…To analyze and quantify ncRNAs in exosomes and microvesicles, they must be isolated from platelet-depleted plasma (Liu et al, 2020). Isolation techniques differ between ncRNAs transported in EVs and those transported in ncRNAprotein complexes (Liu et al, 2020). A commonly used technique is differential centrifugation, although a variety of isolation methods are applied (Witwer et al, 2013).…”
Section: The Non-coding Transcriptome As Biomarker: Challenges and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations